1993
DOI: 10.1111/j.1365-2249.1993.tb06507.x
|View full text |Cite
|
Sign up to set email alerts
|

The induction of cell-associated and secreted IL-1 by iscoms, matrix or micelles in murine splenic cells

Abstract: SUMMARYThe kinetics ofthe expression of membrane-associated IL-1 (mIL-1) and soluble IL-1 (sIL-1) was studied in in vitro stimulated spleen cells from non-primed mice or from mice primed with influenza virus antigens incorporated in the immuno-stimulating complexes (iscoms) or as micelles. Matrix, which is the carrier structure for the antigens in the iscom, was used as a non-antigen stimulus. The IL-1 produced was assayed in an I L-l-dependent cell line and the specificity was demonstrated in a blocking exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A higher degree of Ag internalization observed for iscoms compared with micelles [17] is probably a major factor in evoking this enhanced recall response. Another contributing factor is the capacity of iscoms to increase MHC class II expression and enhance the production of IL-1 [18][19][20]. A third enhancing factor is the secretion of the cytokines measured in this study which was Ag-specific since they were only detected following restimulation with the relevant influenza virus Ag.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…A higher degree of Ag internalization observed for iscoms compared with micelles [17] is probably a major factor in evoking this enhanced recall response. Another contributing factor is the capacity of iscoms to increase MHC class II expression and enhance the production of IL-1 [18][19][20]. A third enhancing factor is the secretion of the cytokines measured in this study which was Ag-specific since they were only detected following restimulation with the relevant influenza virus Ag.…”
Section: Discussionmentioning
confidence: 82%
“…Increased expression of MHC class II molecules, considered to be a requirement for efficient Ag presentation, has been observed in primary stimulation of peritoneal cells and also in primed splenocytes upon restimulation with iscoms, both in vivo and in vitro [19,20]. Some of these data indicate that macrophages have a relevant role in the enhanced immune response to iscom-borne Ag [18,19]. We and others have previously demonstrated that immunization with influenza virus iscoms induces the development of T cells secreting IL-2 and IFN-7 [21][22][23].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…ISCOMs induce production of IL-1β (24, 25), which promotes induction of Th17 CD4 T cells in combination with IL-6 (49), and induction of IL-17+ CD4 T cells has been observed after ISCOM vaccination (50). We did not detect IL-17 production after vaccination with Poly I:C alone, but did detect low and comparable frequencies of IL-17+ CD4 T cells after ISCOM vaccination, with or without Poly I:C in several experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ISCOMs can enhance antigen delivery to APCs when antigen is incorporated into the particle but ISCOMs do not function solely as delivery vehicles, since certain fractions of saponin possess intrinsic adjuvant activity (23). ISCOMs have been shown to induce caspase-dependent cleavage of IL-1β and robust serum production of IL-5, IL-6, GM-CSF and IL-12 p40 (24, 25). As a result, ISCOMs prime potent long-lived antibody responses with a balanced CD4 Th1/Th2 T cell response (26), and low-level induction of CTLs.…”
Section: Introductionmentioning
confidence: 99%